2011
DOI: 10.1007/s00167-011-1420-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Lidocaine on the viability of cultivated mature human cartilage cells: an in vitro study

Abstract: In vitro, local anesthetics containing Lidocaine are significantly more toxic to mature human articular chondrocytes than a saline 0.9% control group. The effect of Lidocaine on the viability of human chondrocytes in vivo needs further investigation. However, based on our in vitro results, cautious use of intra-articular Lidocaine in clinical practice is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 32 publications
5
46
0
10
Order By: Relevance
“…That is particularly evident after cells exposure to 1% L or L+A: in the first case viability was statistically reduced with respect to controls at all observation times, whereas in the second case the viability was significantly reduced only 1 h after exposure. Similar results were obtained by Jacobs et al, (2011) following the exposure of human chondrocytes to 1% L and 1% L + A. These authors speculated that adrenaline may exert a protective effect on chondrocytes but the data presented in the literature are equivocal.…”
Section: Discussionsupporting
confidence: 68%
“…That is particularly evident after cells exposure to 1% L or L+A: in the first case viability was statistically reduced with respect to controls at all observation times, whereas in the second case the viability was significantly reduced only 1 h after exposure. Similar results were obtained by Jacobs et al, (2011) following the exposure of human chondrocytes to 1% L and 1% L + A. These authors speculated that adrenaline may exert a protective effect on chondrocytes but the data presented in the literature are equivocal.…”
Section: Discussionsupporting
confidence: 68%
“…Bupivacaine 0.25% reduced cell viability to 72% in the monolayer cultures but buffering the pH resulted in worsening of cell viability to 22%. Jacobs et al 30 suggested that adrenaline may even have a protective effect on articular cartilage. They harvested articular cartilage from the knees of four human donors and three patients undergoing TKA and cultured the chondrocytes in alginate bead cultures.…”
Section: S204mentioning
confidence: 99%
“…This result is different from the previous report molecularly that is devastating results on chondrocytes after lidocaine treatment. Exposing the chondrocytes to a 50/50 mixture of culture medium and local anesthetics substantially decreased cytotoxicity but still showed high toxicity when compared with the saline group (90% dead cells for lidocaine 2%, P = 0.047) [15]. In this study, the high-toxicity was not presented, considering a 50/50 mixture of culture medium and 2% lidocaine was used.…”
Section: Discussionmentioning
confidence: 87%